Permanent Peripheral Neuropathy - Jacquelyn K. Francis BA; Elizabeth Higgins MD (Journal of Investigative Medicine High Impact Case Reports, 2014)
The health risks and side effects of fluoroquinolone use include the risk of tendon rupture and myasthenia gravis exacerbation, and on August 15, 2013, the Food and Drug Administration updated its warning to include the risk of permanent peripheral neuropathy. We present a case of fluoroquinolone-induced peripheral neuropathy in a patient treated for clinically diagnosed urinary tract infection with ciprofloxacin antibiotic.